Lymphocytic infiltration in stage II microsatellite stable colorectal tumors: A retrospective prognosis biomarker analysis - Sanz-Pamplona, Rebeca; Melas, Marilena; Maoz, Asaf; Schmit, Stephanie L.; Rennert, Hedy; Lejbkowicz, Flavio; Greenson, Joel K.; Sanjuan, Xavier; Lopez-Zambrano, Maria; Alonso, M. Henar; Qu, Chenxu; McDonnell, Kevin J.; et al. (PLoS medicine, 2020)
Recognized clinical risk factors for progression (emergency presentation, poorly differentiated tumor, depth of tumor invasion, and adjacent organ involvement) are insufficient to identify those patients with stage II CRC at higher risk of disease progression [4,5]. [...]a meta-analysis aimed to assess the predictive ability of these signatures revealed that although gene expression signatures may be associated with prognosis, their ability to accurately predict patients’ risk of progression was limited, probably due to the molecular heterogeneity of tumors [7]. [...]the identification of new biomarkers to inform clinical decision-making for adjuvant chemotherapy is needed [8]. Methods Patients and samples The discovery dataset (named ICO/CLX) included a previously described set of 100 patients with colon cancer diagnosed at stage II and MSS paired normal-tumor samples (Colonomics study, “CLX”: www.colonomics.org; NCBI BioProject PRJNA188510). Raw sequence data were filtered based on the TCRβ V, D, and J gene definitions provided by the international ImMunoGeneTics information system (IMGT) database and binned using a modified nearest-neighbor algorithm to merge closely related sequences and remove both PCR and sequencing errors.